Prevalence and associated factors with falls among elderly attended by a Family Health Strategy (ESF) in Itumbiara, GO (Research, Society and Development, 2024)
Purpose: Identify and analyze the factors associated with falls in elderly people registered in three ESFs in Itumbiara. Methods: This is an exploratory, descriptive study carried out with elderly people registered in the ESF. Results: Foram interviewed 24 young people from 60 years of age, being the most common age between 66 and 69 years, in their majority as a complete fundamental ensino and monthly income of 01 minimum wage. 2/3 two interviewees presented comorbidities, most commonly being systemic arterial hypertension, isolated or associated. It was seen that 66.66% of the children suffered a loss in their ability to carry out their daily activities and 75% reported living with someone, and two thirds of the interviewees reported that they suffered at least one last year. Conclusion: We are left with a frequent situation in the ESF of Itumbiara, representing a public health problem, capable of causing consequences that cause morbidity and disability.